MANAGEMENT OF HEALTH, SAFETY AND WELLBEING OF EMPLOYEES IN THE BUSINESS SYSTEM - Živković, Dragić; Todorović, Saša; Bućan, Ivana (Economics of Agriculture, 2015)
Risk assessment and the implementation of measures for a healthy and safe work before the employee starts working, is the basic principle of the prevention of occupational injuries, occupational diseases and diseases related to work. Bearing that in mind, the goal of this paper is to describe the activities of employers and employees in the feld of health, safety and wellbeing of employees in a particular business system as well as to measure progress in safety management by analysing data on occupational injuries, occupational diseases and diseases related to work. The research conducted in this paper is based on information and data collected from the public company "Vojvodinašume" and on the description from literature sources. For the purpose of processing the collected data, we used descriptive statistical methods and the data proper are presented graphically and in tabular form in order to facilitate analysis and comparison. Results of the research showed that the number of occupational injuries in the public company "Vojvodinašume" in the period from 2004 to 2013 reduced, particularly the number of minor injuries. However, the public company "Vojvodinašume", in addition to reducing the number of minor injuries, is obliged to eliminate major and fatal occupational injuries, as well as to enable effective prevention of the occurrence of occupational diseases and diseases related to work.